Invaded range and competitive ability of the newly invasive Polistes dominula compared to that of its native congener species in the Western Cape, South Africa - Benade, P. C. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.